Detection and treatment of hypertension in an inner London community. Issue 4 (December 1976) - Heller, R F
Abstract : A postal survey of a random sample of the population living near St Mary's Hospital, Paddington was taken to determine earlier experience in these people of blood pressure measurement and treatment. Eighty-five per cent of those who could return their questionnaires did so; eighty per cent of the respondents said they had had their blood pressure measured in the past, and 60% reported such a measurement during the previous three years. The respondents aged between 40 and 59 years were invited for a blood pressure screening measurement and 52% responded. Seventy-seven per cent of those found to be hypertensive on screening (systolic greater than or equal to 160 mmHg and/or diastolic greater than or equal to 100 mmHg) said they had had their blood pressure measured during the preceding three years. The reason for the poor control of hypertension in a community, therefore, is more likely to be a failure of doctors to take action on hypertension than a failure to detect it in the first place.